2014
DOI: 10.1007/s10695-014-0018-5
|View full text |Cite
|
Sign up to set email alerts
|

Gilthead seabream (Sparus aurata) response to three music stimuli (Mozart—“Eine Kleine Nachtmusik,” Anonymous—“Romanza,” Bach—“Violin Concerto No. 1”) and white noise under recirculating water conditions

Abstract: This study presents the results of the response of Sparus aurata to three different musical stimuli, derived from the transmission (4 h per day, 5 days per week) of particular music pieces by Mozart, Romanza and Bach (140 dB(rms) re 1 μPa), compared to the same transmission level of white noise, while the underwater ambient noise in all the experimental tanks was 121 dB(rms) re 1 μPa. Using recirculating sea water facilities, 10 groups, 2 for each treatment, of 20 specimens of 11.2 ± 0.02 g (S.E.), were reared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…rhythmic or systematic sound not typically found in the wild) on cultured fish. For example, it has been demonstrated that musical stimuli positively influence growth performance, feeding efficiency and stress reduction on common carp ( Cyprinus carpio ), 162‐165 gilthead seabream 166,167 and rainbow trout, 168 mostly reared in recirculating water systems. Similarly, Catli et al 169 reported that slow tempo music‐induced positive effects on growth performance and feed intake of turbot ( Scophthalmus maeotica ), whereas fast tempo music‐induced negative effects and stress in this species.…”
Section: Environmental Enrichment Strategiesmentioning
confidence: 99%
“…rhythmic or systematic sound not typically found in the wild) on cultured fish. For example, it has been demonstrated that musical stimuli positively influence growth performance, feeding efficiency and stress reduction on common carp ( Cyprinus carpio ), 162‐165 gilthead seabream 166,167 and rainbow trout, 168 mostly reared in recirculating water systems. Similarly, Catli et al 169 reported that slow tempo music‐induced positive effects on growth performance and feed intake of turbot ( Scophthalmus maeotica ), whereas fast tempo music‐induced negative effects and stress in this species.…”
Section: Environmental Enrichment Strategiesmentioning
confidence: 99%